The impostor phenomenon among surgeons and surgeons in training: a scoping review - Chunlan Jin; Jian Ling; Zuhuan Xu; Tao Lin; Weiqin Chen (BMC Medical Education)
Abstract Background The impostor phenomenon (IP), is a condition in which people think they are incapable of success and tend to attribute their success to external causes such as luck, error, or knowing the appropriate individuals. It has been confirmed as a contributor to burnout for practicing physicians, residents, and medical students. The purpose of this scoping review is to describe the prevalence and scope of IP among surgeons and surgeons in training, in order to determine gaps that can be addressed in future research. Methods Searches were conducted in the following databases: Embase, PubMed, Medline, CINAHL (Cumulative Index to Nursing and Allied Health Literature), Cochrane Library, Web of Science, PsycINFO, Google Scholar, and ProQuest from inception to 30 June 2024. Two investigators independently assessed the articles based on the inclusion and exclusion criteria. All titles and abstracts meeting the inclusion criteria were carefully reviewed for the full text. The individual screening results were compared, and any discrepancies were discussed with a third investigator and a final consensus for further analysis. Results The Clance Impostor Phenomenon Scale (CIPS) was used to assess the prevalence in the included studies. The prevalence of IP among surgeons and surgeons in training ranged from 27.5 to 100%. Women were more prone to suffer from IP when compared to their male counterparts. Most literature also showed that female surgeons reported statistically higher in IP scores than males. Level of education and academic achievements were also associated with IP. Conclusions This scoping review identified the published literature on IP among surgeons and surgeons in training and focused on the existing research objects to discover the gaps in the current research. Future directions may focus on early interventions aimed at identifying and managing IP.